High velocity impact responses of sandwich panels with metal fibre laminate skins and aluminium foam core. (February 2017) - Liu, Chengjun; Zhang, Y.X.; Ye, L.
Highlights: Intensive investigation of the high velocity impact responses of newly designed sandwich panels with aluminium (AL) foam core and metal fibre laminate (FML) skins. Gas gun impact tests at a velocity of 210 m/s. Study on the effect of the thickness of the foam core and FML skin on the impact resistance Development of a finite element model for effective numerical modelling of the impact behaviour of the sandwich panels Parametric study on the effect of the shape of projectile and impact angle on the impact behaviour of the sandwich panels using the FE model. Abstract: In this paper, high velocity impact responses of newly designed sandwich panels with aluminium (AL) foam core and metal fibre laminate (FML) skins, which are comprised of aluminium sheets and plain woven E glass fibre composite plies are investigated. Gas gun impact tests were conducted to investigate the high velocity impact response of the panels subjected to the impact from a steel ball bearing at an impact velocity of around 210 m/s. The effect of the thickness of the foam core and FML skin on the impact resistance of the panels is also investigated via experimental study. A finite element model is developed for effective numerical modelling of the impact behaviour of the sandwich panels using the commercially finite element software ANSYS LS-DYNA for more extensive study of the impact response of the sandwich panels. The simplified Johnson Cook material model, the composite damage material model based on the Chang-Chang criteria, and the crushable foam material model are used to model the aluminium sheets, composite plies and the AL foam respectively. Three types of contact algorithms, i.e. the erosion contact type, the tie-break contact type and the general 3D contact type are employed to define the various contacts during the impact and to model the delamination between the FML layers and debonding between the FML skin and the AL foam. The finite element model is validated by comparing the simulated impact behaviour to that from experimental for a sandwich panel subjected to high speed impact and demonstrated to be effective and accurate. The effect of the shape of projectile and impact angle on the impact behaviour of the sandwich panels is studied using the developed finite element model. The research findings are summarized and concluded finally.